2008
DOI: 10.1258/ijsa.2007.007208
|View full text |Cite
|
Sign up to set email alerts
|

Study on Peer-Led School-Based HIV/AIDS Prevention among Youths in a Medium-Sized City in China

Abstract: HIV/AIDS epidemic is crucial in China; however, few studies were performed on youths. This study was performed to examine the effectiveness of peer-led HIV prevention intervention on HIV-related knowledge, attitudes and behaviour intention in senior high-school students in San-ming, a medium-sized city in Fujian province. Three thousand and sixty-eight students completed self-administered questionnaires before and after intervention, of which 981 students (the intervention group) accepted peer-led HIV/AIDS pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
2
13
0
6
Order By: Relevance
“…The result of this research indicates that nearly 28% of unmarried rural-to-urban female migrants report having had premarital sex, which is similar to the finding among three major cities in China in 2011 [14]. In relation to RH and STI/AIDS knowledge, as compared to studies conducted in their urban peers using the similar questionnaire [31], [32], our results showed that the SRH related information among unmarried rural-to-urban female migrants are poorer, especially the information about STI/AIDS. The results suggest an urgent need for STI/AIDS and RH related interventions for the unmarried rural-to-urban female migrants.…”
Section: Discussionsupporting
confidence: 76%
“…The result of this research indicates that nearly 28% of unmarried rural-to-urban female migrants report having had premarital sex, which is similar to the finding among three major cities in China in 2011 [14]. In relation to RH and STI/AIDS knowledge, as compared to studies conducted in their urban peers using the similar questionnaire [31], [32], our results showed that the SRH related information among unmarried rural-to-urban female migrants are poorer, especially the information about STI/AIDS. The results suggest an urgent need for STI/AIDS and RH related interventions for the unmarried rural-to-urban female migrants.…”
Section: Discussionsupporting
confidence: 76%
“…15 High school students in China have long school hours (5.4 days in school per week and 7.6 lessons/day 28 ) and heavy pressure for academic achievement (2 h/day on homework 28 ); thus, minimal interruption to school is critical to ensure the sustainability of a school-based health promotion programme in this context. Fourth, students were educated in groups regarded as small in China, which was associated with greater increases in knowledge, altered attitudes and intentions to change behaviour than those in larger groups in the peer education study 19 because small groups facilitate cooperative learning, discussion and communication. 29 Comparison with studies in China was limited because there has been only one study that used a teacher-led organised exercise to prevent obesity in adolescents, and physical activity outcome was not reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In China, peer education has been effective in promoting knowledge, attitudes and intention to change behaviour in AIDS prevention. 19 However, no studies have evaluated the effect of peer education on physical activity and sedentary behaviours. Therefore, we conducted a pilot study from September 2010 to May 2011in four junior high schools in urban Beijing, China, to test the feasibility of a peer-led education programme in changing obesity-related behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…In justify the behavioral intention, with respect to the model, due to the increasing score of: attitude, subjective norms, and perceived behavioral control, therefore increasing in behavioral intention toward safe sex can be expected. To explain the aim of the study regarding rate of effectiveness of the conducted training programs, the overall estimates of the results indicated the positive impact of theory-based educational intervention toward safe sexual behaviors intention among substance users covered by A and the results obtained in this study were consisted with other similar studies (23,25,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 53%